2017
DOI: 10.5530/pj.2017.2.26
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Analysis and Thermal Behavior of Salvia hispanica, Nigella sativa and Papaver somniferum Seeds

Abstract: Introduction: Salvia hispanica L., Nigella sativa L. and Papaver somniferum L. are involved in opiate-dependent behavior. It is known that the seeds of these three herbs contain high amounts of antioxidants, which are helpful in disease prevention, but further research is needed on some of their other phytochemical components (terpene alkaloids, benzoquinones and others), which are claimed to affect human opioid receptors. Methods: Seeds from the three afore mentioned plants have been studied by ATR-FTIR vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…The absence of the bands at 1015 cm -1 and ~878 cm -1 (apart from that of 795 cm -1 ) is also a common feature with the Asteraceae (unpublished results). The absence of bands at 1574, 1563, 1336, 1138, 1076, 857, 778 and 757 cm -1 has been previously observed for Salvia hispanica L. [28]. Absorbance (a.u.…”
Section: Vibrational Characterizationsupporting
confidence: 52%
“…The absence of the bands at 1015 cm -1 and ~878 cm -1 (apart from that of 795 cm -1 ) is also a common feature with the Asteraceae (unpublished results). The absence of bands at 1574, 1563, 1336, 1138, 1076, 857, 778 and 757 cm -1 has been previously observed for Salvia hispanica L. [28]. Absorbance (a.u.…”
Section: Vibrational Characterizationsupporting
confidence: 52%
“…The FTIR spectra of the three chia samples under the study are depicted in Figure 5, and their main bands are summarized in Table 2. It can be observed that they are similar, in particular, the samples exposed to light for 24 and 48 h. A large number of peaks appeared in the region from 1000 to 3000 cm −1 , indicating that chia microgreens have a rich chemical composition (proteins, lipids, carbohydrates) [18]. More precisely, the band located around 3290 cm −1 represents N-H stretching vibrations that are caused by proteins [20].…”
Section: Effect Of Illumination On Ftir Spectramentioning
confidence: 74%
“…Additionally, the fingerprint region between 1000 and 1500 cm −1 is where amide II and the functional groups of nucleic acid and carbohydrates contribute to these absorption bands. A large number of peaks appeared in the region from 1000 to 3000 cm −1 , indicating that chia microgreens have a rich chemical composition (proteins, lipids, carbohydrates) [18]. More precisely, the band located around 3290 cm −1 represents N-H stretching vibrations that are caused by proteins [20].…”
Section: Effect Of Illumination On Ftir Spectramentioning
confidence: 98%
See 1 more Smart Citation
“…It is to be noted that the peaks associated with the phytyl chain of tocopherols (about 2900 cm −1 ) did not show considerable difference in their intensity. The sharp peak noticed at 1744 cm −1 was a consequence of vibrations from (CO) ester of terpene alkaloids (Carrión-Prieto et al 2017). However, minor contribution of vibrations from δ(N -H) (amide III) of proteins to the peak at 1240 cm −1 could not be over-ruled.…”
Section: Ftir Spectroscopymentioning
confidence: 94%